Regional Thrombolysis with Tenecteplase During Extracorporeal Membrane Oxygenation: A New Approach for Left Ventricular Thrombosis. Issue 6 (5th May 2015) - Sangalli, Fabio; Greco, Gianluca; Galbiati, Lucia; Formica, Francesco; Calcinati, Serena; Avalli, Leonello
Abstract We present the case of a woman assisted with veno‐arterial extracorporeal membrane oxygenation (v‐a ECMO) for postischemic cardiogenic shock, who developed left ventricular thrombosis despite systemic anticoagulation and left ventricular apical venting. We successfully achieved local thrombolysis with tenecteplase administered through the venting cannula to obtain local thrombolysis while reducing systemic effects to a minimum. The procedure was effective with mild systemic bleeding and the patient was successfully weaned off the extracorporeal support a few days thereafter. doi: 10.1111/jocs.12556 (J Card Surg 2015;30:541–543)